2020
DOI: 10.15406/japlr.2020.09.00346
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical indicators in trypanosomiasis infections

Abstract: Biochemical assessment of the body fluids gives an indication of the functional state of the various body organs and biochemical changes in the fluids which result from trypanosomiasis infections depend on the species of the parasite, its virulence, susceptibility of the host and the period of infection during which the samples are taken. Evaluations of biochemical parameters are usually done on specimen that includes serum or plasma and cerebrospinal fluid (CSF) obtain from infected animals or humans. Abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…This consequently resulted in a pronounced drop in testosterone levels in IG, (negative correlation with the infection duration). Similar results were noted before in T. gambiense-infected human [21] , T. b. brucei and T. evansi-infected rams [22] , and T. evansiinfected camels [23] . On the other hand, cytokinesinduced pituitary inflammation, pyrexia, anorexia, and anemia, and the trypanosomal proteases may be other causes of GnRH depletion and hypothalamus-pituitarygonadal axis dysfunction.…”
Section: Discussionsupporting
confidence: 90%
“…This consequently resulted in a pronounced drop in testosterone levels in IG, (negative correlation with the infection duration). Similar results were noted before in T. gambiense-infected human [21] , T. b. brucei and T. evansi-infected rams [22] , and T. evansiinfected camels [23] . On the other hand, cytokinesinduced pituitary inflammation, pyrexia, anorexia, and anemia, and the trypanosomal proteases may be other causes of GnRH depletion and hypothalamus-pituitarygonadal axis dysfunction.…”
Section: Discussionsupporting
confidence: 90%
“…Trypanosome parasitaemic cattle had signi cantly lower serum albumin and numerically higher serum globulin in agreement with previous studies on effect of trypanosome infection on serum protein pro le of cattle and other animals(Ismail and Eman, 2014; Ozdek et al, 2020) Akinseye et al (2020). reviewed the biochemical indicators in trypanosomiasis and indicated that decreased total protein, and albumin and increased globulin levels were consistent ndings.…”
supporting
confidence: 89%
“…The mechanisms by which trypanosomes establish, multiply, and inundate the host with heavy parasitaemia is believed to involve the variable surface glycoprotein (VSG) genes which constitute about 10% of the trypanosome genome and of which only one is expressed at any given time (Igbokwe, 2018). This gene pool provides the molecular resources for antigenic variation which enables the parasite to discard the surface coat regularly, evade recognition by host immune system and endogenous trypanocidal factors (Abenga et al, 2017;Akinseye et al, 2020;Aresta-Blanco et al, 2019). In addition, trypanosomes utilize host nutrient supplies (carbohydrates, proteins, lipids, and micronutrients) for their metabolism (Igbokwe, 2018) and release metabolites some of which contribute to the pathogenesis of the disease (Mishra et al, 2017;Getahun et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in AST levels might be attributed to tissue damage induced by trypanosomes, as well as the destruction of the parasite by the host immune system, resulting in the release of trypanosomal AST (Takeet and Fagbemi, 2009;Pandya et al, 2018a). This rise in ALT levels could be due to hepatic damage caused by the parasite (Akinseye et al, 2020).…”
Section: Discussionmentioning
confidence: 99%